Nitrogen sources differentially affect respiration, growth, and carbon allocation in Andean and Lowland ecotypes of Chenopodium quinoa Willd - Jerez, María Paz; Ortiz, José; Castro, Catalina; Escobar, Elizabeth; Sanhueza, Carolina; Del-Saz, Néstor Fernández; Ribas-Carbo, Miquel; Coba de la Peña, Teodoro; Ostria-Gallardo, Enrique; Fischer, Susana; Castro, Patricio Alejandro; Bascunan-Godoy, Luisa (Frontiers in Plant Science, 2023)
Chenopodium quinoa Willd. is a native species that originated in the High Andes plateau (Altiplano) and its cultivation spread out to the south of Chile. Because of the different edaphoclimatic characteristics of both regions, soils from Altiplano accumulated higher levels of nitrate (NO3−) than in the south of Chile, where soils favor ammonium (NH4+) accumulation. To elucidate whether C. quinoa ecotypes differ in several physiological and biochemical parameters related to their capacity to assimilate NO3− and NH4+, juvenile plants of Socaire (from Altiplano) and Faro (from Lowland/South of Chile) were grown under different sources of N (NO3− or NH4+). Measurements of photosynthesis and foliar oxygen-isotope fractionation were carried out, together with biochemical analyses, as proxies for the analysis of plant performance or sensitivity to NH4+. Overall, while NH4+ reduced the growth of Socaire, it induced higher biomass productivity and increased protein synthesis, oxygen consumption, and cytochrome oxidase activity in Faro. We discussed that ATP yield from respiration in Faro could promote protein production from assimilated NH4+ to benefit its growth. The characterization of this differential sensitivity of both quinoa ecotypes for NH4+ contributes to a better understanding of nutritional aspects driving plant primary productivity.